Dinamika Peradaban Islam: Kajian Sejarah Pemikiran, Politik dan Budaya - Halim, Abdul; Syarif, Zainuddin (Kartika: Jurnal Studi Keislaman, 2026)
Islamic civilization is the result of a dynamic interaction between thought, politics, and culture that has developed throughout history. This article aims to analyze how these three pillars are intertwined in shaping the character of Islamic civilization from classical to contemporary times. The study is conducted using a historical-analytical approach by tracing the development of theological and philosophical thought, political configurations from the Khulafa’ al-Rāsyidīn era to the era of the modern nation-state, and cultural dynamics that reflect the process of acculturation of Islam with local traditions. The research findings indicate that the progress of Islamic civilization occurs when thought is creative and rational, political structures support intellectual freedom, and culture develops cosmopolitanly. Conversely, stagnation of thought and political authoritarianism have a direct impact on cultural decline. This article emphasizes that the revival of Islamic civilization today demands an integrative reconstruction of these three dimensions through an interdisciplinary and contextual approach.